Students Empowerment in Mathematics Classroom: Perception, Strategies, and States - Dhakal, Bed Prasad (Innovative Research Journal, 2022)
Whatever the existing teaching-learning practices of mathematics education in our classroom, it is time to escalate its effectiveness through sincere exploration of students’ empowerment. Empowering our students in the mathematics classroom is psychological, strategic, and contingent on both mathematics teachers and students. This article argues that the exploration of understanding students’ empowerment, empowering strategies, and state of empowered mind are not fully studied yet. Capturing the belief, understanding, perception, and practices of students’ empowerment in mathematics teaching and learning is the core concern of this paper. The secondary-level mathematics teachers from the community schools of Kathmandu valley were purposively selected. Descriptive exploration was made to discuss the information on three key focuses; perception of students’ empowerment, strategies for empowerment, and states of empowered students within the classroom premises. The opportunity for collaborative and cooperative engagement which accept the individual voice of students in the mathematics classroom is perceived as the strategy for students’ empowerment. Sufficient cognitive, as well as effective actions that help to build the students’ strength in learning mathematics, are the fundamental empowering strategies, and the condition of happiness, satisfaction and on-task behavior are the states of empowered students. Policymakers, academicians, and even managers would take benefit from the finding of this article. There are still many spaces to reduce the gap between existing and expected strategies for students’ empowerment in the mathematics classroom.